Balanced Nutrition Programme: A school-based education initiative from Turkey - AKTAÇ, ŞULE; SABUNCULAR, GÜLEREN (My University, 2019)
Nutrition has a big impact on physical and mental development through all life stages, especially in childhood. Nutrition habits during childhood can impact later life preferences and health status, (1) and school-based nutrition interventions are very important to build healthy lifestyle in early life. (2) Moreover, schools have a unique environment for the implementation and evaluation of these interventions. Also, a body of evidence shows balanced nutrition can contribute student’s academic performance. (3) School-aged children’s food preferences and nutrition habits can be impacted by peers, other students, teachers, family members and media. School based nutrition education programmes can help to build healthy eating habits and active life style with education materials which cover age-related activities and games. The Balanced Nutrition Education Programme was established in 2011 by the Sabri Ülker Food Research Foundation in cooperation with Ministry of National Education, in Turkey. Education materials of Balanced Nutrition Project has developed and adapted to Turkish from British Nutrition Foundation’s Food a Fact of Life Project. In 2011 programme was performed in 2nd and 4th grade students, afterwards with the success of program, students from preschool up to 4th grade were involved so far. Balanced Nutrition Programme has reached nearly 6 million individuals via students, teachers and families. To evaluate the impact of the Balanced Nutrition Education Programme, for first a research has conducted in 2014. (4) According to this research, programme improved nutrition and physical activity status of children and the second research to evaluate the impact of the project is runned.